Code Enforcement Of Sanctions For Notary Who Having Multiple Offices - Abiem Pandya Prasojo; Anis Mashdurohatun; Ngadino Ngadino (Jurnal Akta, 2019)
In every office attached to someone will be accompanied by moral rules called code of ethics as well as the notary office. Code of conduct notary entire moral code is determined by the association organization "Indonesian Notary Association" (INI), where applicable, and must be obeyed by all members of the association as well as others who have positions of notary. Notary is necessary to know and understand the code of conduct notary. This code of conduct govern all actions of what can be regarded as a violation of the code of conduct and what sanctions if violated the code of conduct. In practice, a notary public notary supervised by the board of trustees. This oversight is necessary so that the notary did not ignore the majesty and dignity of the profession.The method used in this research is normative. The data used are primary data and secondary data. Primary data in the form of research conducted in the field related to the object of research and data secondary, namely in the form of legislation, library, archives, expert opinions and regulations associated with the object of research.Discussion of the results shows that the sanction of conduct for notaries who have multiple offices are in violation of the code of conduct notary office. based on the above factors, it is important to know what is an indication of an offense involving the notary in the notary office area coverage authorized by a notary office code of ethics. Should the effort of the board of trustees for providing information about the code of conduct for all notaries to avoid misunderstandings about the ban notaries and exclusion. Therefore the role of the board of honor in the enforcement of the code of ethics notary must be implemented properly and in accordance with the applicable rules.Keywords: Notary Code; Honor Council; Office of the Associate; Notary.